The state of erythrocytes during hypertonic and posthypertonic shock - Chabanenko, Olena; Yershova, Natalia; Shpakova, Natalia (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(4):299